ANALISIS KINERJA KEUANGAN PT BANK PERKREDITAN RAKYAT JWALITA DI KABUPATEN TRENGGALEK - Putria, Nabella Oksita; Wahyudi , Muhammad Sri (Journal of Financial Economics & Investment, 2023)
Bank is a financial institution whose operations require good financial performance in order to run well.  Similarly, the Rural Bank in its operations must be carried out properly as well as the dominant and rapidly growing conventional banks in Indonesia. One way for the bank to run well is to pay attention to its financial performance. The financial ratios used are the RGEC method which includes NPL, LDR, Good Corporate Governance, ROA, BOPO and Capital taken from the annual report for the 2019-2021 period. The type of data used in this research is primary data using virtual ethnography method. Based on the analysis of the financial ratios of PT Bank Perkreditan Rakyat Jwalita, the financial performance in the RGEC method results in a very good financial condition of the Bank in accordance with the criteria of Bank Indonesia.